Efficacy of double filtration plasmapheresis in hyperlipidemia acute pancreatitis: a retrospective observational study - Rong Qin; Yibei Liu; Rui Ding; Minhui Yang; Yun Huang; Xujia Chen; Feng Zhang; Yanting Liu; Hongping Jia; Yiyao Duan; Lifang Zhou; Hui Wang (Lipids in Health and Disease)
Abstract Background This study examines the role and effectiveness of double filtration plasmapheresis (DFPP) in managing hyperlipidemiclipidemic acute pancreatitis (HLAP). Methods Comparative analysis was conducted between two groups: one treated with DFPP and one without. Comparative parameters included blood lipid levels, inflammatory factors, vital signs, disease severity scores, and complication rates. Results A total of 97 HLAP patients were included in the study. Within-group analysis revealed significant pre- and post-treatment changes in total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), white blood cell count (WBC), neutrophil percentage (N%), systemic immune-inflammation index (SII), mean arterial pressure (MAP), bedside index for severity in acute pancreatitis (BISAP), and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores in the DFPP group (P < 0.05). In contrast, the without DFPP group showed significant changes in TC, TG, LDL-C, WBC, N%, SII, systemic inflammation response index (SIRI), panimmune-inflammation value (PIV), respiration rate (RR), and APACHE II scores (P < 0.05). Significant differences in TC, TG, HDL-C, LDL-C, and RR were found between the DFPP and without DFPP groups (P < 0.05). The DFPP group exhibited greater reductions in TG levels and more individual variability. In terms of complications, the rate of systemic inflammatory response syndrome (SIRS) differed significantly between the groups (P < 0.05). Conclusions DFPP can significantly improve short-term outcomes, reduce lipid levels, and reduce the incidence of complications such as SIRS in HLAP patients compared with those not receiving DFPP treatment. The clinical utility of DFPP is considerable, and further exploration and implementation of this method are warranted.